The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.20944/preprints202008.0677.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Illumina Versus Nanopore 16S rRNA Gene Sequencing of the Human Nasal Microbiota

Abstract: Illumina and nanopore sequencing technologies are powerful tools that can be used to determine the bacterial composition of complex microbial communities. In this study, we compared nasal microbiota results at genus level using both Illumina and nanopore 16S rRNA gene sequencing. We also monitored the progression of nanopore sequencing in the accurate identification of species, using pure, single species cultures, and evaluated the performance of the nanopore EPI2ME 16S data analysis pipeline. Fifty-nine nasal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Literature shows that the use of Oxford Nanopore's commercial barcoding primers also potentially interfere with one's capacity to detect certain bacterial taxa in complex samples. Corynebacterium, Pseudomonas and Bifidobacterium have been reported to be some of the affected genera (9,10,25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature shows that the use of Oxford Nanopore's commercial barcoding primers also potentially interfere with one's capacity to detect certain bacterial taxa in complex samples. Corynebacterium, Pseudomonas and Bifidobacterium have been reported to be some of the affected genera (9,10,25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, size range cutoffs chosen to filter reads certainly have an impact on the number of reads retrieved in a given experiment. Thus, most reports for microbial community analysis using 16S we found applied different Q Score thresholds (usually Q Score > 7) and variable cutoff values (e.g., 1,300-1,950 bp, <1,700 bp, 1,400-1,700 bp, and 1,350-1,650 bp) (9,10,25,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And MinION and Illumina platforms generated comparable results from different biofluids including human nasal samples. 25 Many metagenomics studies adopt commercial kits for DNA extraction and reports demonstrated that manual method processed fecal samples better captures the microbial diversity. 26 In this study we compared two manual methods of DNA extraction for further processing.…”
Section: Discussionmentioning
confidence: 99%